Analysis and Evaluation of Clinical Communication in the Surgical Intensive Care Unit. Issue 1 (June 2014) - Napoli, Nicholas J.; Barnhardt, William; Young, Jeﬀrey; Barnes, Laura
For decades, emergency departments have become increasingly unable to meet escalating patient demands. In order to allow emergency departments to operate beyond their designed capacity, major eﬀorts have gone into improving their work-ﬂow, eﬃciency, and quality of care. Many studies have show that ineﬃciencies and error in a clinical setting are linked to communications. As a means to improve the quality of care for trauma patients, this study examines the present communication systems for diﬀerent admission pathways to the University of Virginia's Surgical Intensive Care Unit (SICU) and recommends a new design for critical operations. The evaluation and analysis of this new design will identify critical factors, including potential communication modalities, implementation details, potential key clinician roles, and in which processes the new system will be useful. Our objective is to design a real-time communication infrastructure for operations within a critical care unit by an informed design process.